EDITORIAL - Martins, Lauber (Revista de Engenharia Térmica, 2023)
The editorial of Thermal Engineering of this issue continues the discussion on scientific research needs in vital areas in which thermal engineering has important participation. The main goal is to motivate the readers, within their specialties, to identify possible subjects for their future research. The ever growing global energy demand requires de development of alternative fuels. That demand has propelled the search for viable sources of clean energy. The investment in research and development in renewable energy has increased in recent years and the economic viability of those sources of energy has become closer to reality. One of the major downsides of the production of biofuels from vegetal sources is the use of land that would be used to produce food to produce agricultural products that will be used to produce fuel. Taking that context in consideration, the development of a methodology economically viable that produces biofuels and bioproducts from microalgae is a solution that meets the criteria aforementioned. Energy applications is the biggest assets of microalgae growth; it can generate biohydrogen, biodiesel and biogas. Biodiesel is produced from microalgae oil, gas methane is produced by the anaerobic digestion (AD) of microalgae biomass and biohydrogen is produced by photolysis in the photochemical step of the photosynthesis. Hydrocarbons with similar composition of jet fuel can be obtained from microalgae by distillation. Other than that, microalgae can be used as supplies for pharmaceutical companies with high added value product as carotenoids, for example. Microalgae can be produced in photobioreactos (PBR’s). PBR’s are designed in a way that do not compete with the use of land for produce. The mission of Thermal Engineering is to document the scientific progress in areas related to thermal engineering (e.g., energy, oil and renewable fuels). We are confident that we will continue to receive articles’ submissions that contribute to the progress of science.